Quantitative assessment of placental perfusion by three-dimensional power Doppler ultrasound for twins with selective intrauterine growth restriction in one twin. (July 2018) - Sun, Wei; Liu, Jingyi; Zhang, Ying; Cai, Ailu; Yang, Zeyu; Zhao, Yili; Wang, Yu; Cao, Zhe; Wei, Qiuju
Abstract: Objective: We quantitatively assessed placental perfusion using three-dimensional (3D) power Doppler ultrasound for twins with selective intrauterine growth restriction (sIUGR) in one twin. Study Design: A prospective cross-sectional study was performed for 104 normal monochorionic diamniotic twins and 30 twins with sIUGR. Twins with sIUGR were divided into two groups: in group I (19 twins), both fetuses had continuous forward end-diastolic blood flow in the umbilical artery; in group II (11 twins), the smaller fetus had a loss or a reverse end-diastolic blood flow in the umbilical artery, but the larger fetus had continuous forward end-diastolic blood flow. Volume data of the placenta was acquired in each twin at the plane where the umbilical cord entered the placenta by 3D power Doppler ultrasound, and imaging software was used to calculate the placental vascularization index (VI), flow index (FI), and vascularization flow index (VFI). Results: Among smaller fetuses, the sIUGR and control groups showed significant differences in VI and VFI, as well as significant differences between sIUGR group II and control group in FI. No such differences in placental perfusion were found among larger fetuses. Conclusions: 3D power Doppler ultrasound could sensitively display the varying degrees of changes in placental perfusion, which could be used for clinical monitoring of placental perfusion in sIUGR twins.